Upgrading waste plastic derived pyrolysis gas via chemical looping cracking–gasification using Ni–Fe–Al redox catalysts - Huang, Jijiang (2022)
A novel chemical looping cracking–gasification process was investigated to produce separate H2 and syngas from plastic-derived pyrolysis gas over synthetic Ni–Fe–Al redox catalysts. The non-condensable pyrolysis gas was catalytically cracked at 800 °C, followed by catalyst regeneration with steam. The highest activity was obtained over NiFeAl (molar Ni:Fe:Al = 1:1:1), producing concentrated H2 (83.1 vol%, 0.46 mol g(Ni+Fe)−1) and coke intermediate (232.1 wt%) from cracking. During the steam gasification stage, coke removal efficiency of 96% was obtained with a high syngas yield of 0.89 mol g(Ni+Fe)−1. With equimolar Ni/Fe, increasing Al/(Ni+Fe) ratio led to decreased catalyst activity due to enhanced metal–support interaction. Plausible reaction mechanisms were proposed to interpret the catalytic effects on tuning the morphologies, chemical structure and activity of the coke deposits. This work demonstrates the important role of Ni–Fe–Al catalysts on the production of H2 and syngas via chemical looping cracking–gasification process.